Bioengineering of spider silks for the production of biomedical materials - Bittencourt, Daniela Matias de C.; Oliveira, Paula; Michalczechen-Lacerda, Valquíria Alice; Rosinha, Grácia Maria Soares; Jones, Justin A.; Rech, Elibio L. (Frontiers in Bioengineering and Biotechnology, 2022)
Spider silks are well known for their extraordinary mechanical properties. This characteristic is a result of the interplay of composition, structure and self-assembly of spider silk proteins (spidroins). Advances in synthetic biology have enabled the design and production of spidroins with the aim of biomimicking the structure-property-function relationships of spider silks. Although in nature only fibers are formed from spidroins, in vitro, scientists can explore non-natural morphologies including nanofibrils, particles, capsules, hydrogels, films or foams. The versatility of spidroins, along with their biocompatible and biodegradable nature, also placed them as leading-edge biological macromolecules for improved drug delivery and various biomedical applications. Accordingly, in this review, we highlight the relationship between the molecular structure of spider silk and its mechanical properties and aims to provide a critical summary of recent progress in research employing recombinantly produced bioengineered spidroins for the production of innovative bio-derived structural materials.